Greek museum media visibility and museum visitation: an exploration of cultural agenda setting [mediensichtbarkeit griechischer museen und museumsbesuche: eine untersuchung zum kulturellen agenda-setting] - Bantimaroudis, Philemon; Zyglidopoulos, Stelios C.; Symeou, Pavlos C.; Bantimaroudis, Philemon; Zyglidopoulos, Stelios C. (My University, 2010)
This project investigates the classic agenda-setting hypothesis in the context of the Greek cultural market. It is hypothesized that Greek museums with higher visibility in newspaper content are related to higher visitation than museums with lower media visibility. Because of the nature of the Greek cultural market-Greece receives more than 10 million tourists during the summer months-several variables are controlled for, such as the seasonality of visitation, the type of governance of the organization, one-time events, such as the Olympic Games, which took place in the summer of 2004, and promotion initiatives undertaken by museums. When controlling for such culturally specific variables, there is evidence supporting the agenda-setting hypothesis within the Greek cultural market.
Keywords: Advertising for museums; Cultural agenda setting; Cultural marketing